2020
DOI: 10.1093/biosci/biaa134
|View full text |Cite
|
Sign up to set email alerts
|

Forest Restoration and Fuels Reduction: Convergent or Divergent?

Abstract: For over 20 years, forest fuel reduction has been the dominant management action in western US forests. These same actions have also been associated with the restoration of highly altered frequent-fire forests. Perhaps the vital element in the compatibility of these treatments is that both need to incorporate the salient characteristics that frequent fire produced—variability in vegetation structure and composition across landscapes and the inability to support large patches of high-severity fire. These charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(65 citation statements)
references
References 122 publications
3
56
0
Order By: Relevance
“…Long-term forest conservation may require integrating the lower range of historical variation in tree density, basal area, and AGLB to adapt to novel ecological conditions. While this approach may converge with forest conservation and fire hazard reduction goals (Stephens et al 2020a), it will require adjusting expectations regarding the contribution of forests toward greenhouse gas reduction goals. We found that the Sierra Nevada/ southern Cascade region may be unable to support AGLB >40 Mg ha −1 by 2069, a value approximately 25% of current AGLB stocks (supplementary table 3).…”
Section: Discussionmentioning
confidence: 99%
“…Long-term forest conservation may require integrating the lower range of historical variation in tree density, basal area, and AGLB to adapt to novel ecological conditions. While this approach may converge with forest conservation and fire hazard reduction goals (Stephens et al 2020a), it will require adjusting expectations regarding the contribution of forests toward greenhouse gas reduction goals. We found that the Sierra Nevada/ southern Cascade region may be unable to support AGLB >40 Mg ha −1 by 2069, a value approximately 25% of current AGLB stocks (supplementary table 3).…”
Section: Discussionmentioning
confidence: 99%
“…Forest management interventions to increase the resilience of these ecosystems to expected global changeinduced disturbances (e.g., wildfires, droughts, and/or insects/disease) may need to explicitly address live tree density reduction across strategic-scales 40 . Without large-scale disturbances, improved low grade fiber markets, and/or forest management policy initiatives, we can expect the current trends of increasing RD to carry on as more stands continue their progression through stand development into high RD conditions (i.e., selfthinning-induced mortality) unless disturbances occur.…”
Section: Discussionmentioning
confidence: 99%
“…Fuel treatments that modify within-stand structure to remove small trees and reduce surface fuels while retaining large, more fire-resistant trees and variable stand structure (Stephens et al 2021) are most appropriate in dry pine, dry to moist mixed-conifer forests and oak woodlands, particularly where there is evidence that older fire-resistant species have been or are being replaced by younger fire-sensitive species (e.g., Yocom-Kent et al 2015). This mirrors the fine-to meso-scale (i.e., 1-10,000 ha) heterogeneity in forest structure that characterized these frequent-fire forest types historically (Hessburg et al 2019.…”
Section: Box 1 Defining Restorative and Adaptive Managementmentioning
confidence: 99%